Mechanisms of action of ribavirin against distinct viruses - Graci, Jason D.; Cameron, Craig E. (Reviews in medical virology, 2006)
The nucleoside analogue ribavirin has antiviral activity against many distinct viruses both in vitro and in vivo. Five distinct mechanisms have been proposed to explain the antiviral properties of ribavirin. These include both indirect mechanisms (inosine monophosphate dehydrogenase inhibition, immunomodulatory effects) and direct mechanisms (interference with RNA capping, polymerase inhibition, lethal mutagenesis). Recent concerns about bioterrorism have renewed interest in exploring the antiviral activity of ribavirin against unique viruses. In this paper, we review the proposed mechanisms of action with emphasis on recent discoveries, as well as the implications of ribavirin resistance. Evidence exists to support each of the five proposed mechanisms of action, and distinct virus/host combinations may preferentially favour one or more of these mechanisms during antiviral therapy. Copyright © 2005 John Wiley & Sons, Ltd.